ANALISIS KONTEN EDUKASI INFLUENCER INSTAGRAM TERHADAP PENGETAHUAN, SIKAP DAN PERILAKU GIZI SEIMBANG FOLLOWERS-NYA - Aulia Rizki Rinalda; Khoirul Anwar (Pontianak Nutrition Journal (PNJ), 2023)
Instagram content is a source of information that can be presented by content creators or influencers who have the power to influence and lead their followers' opinions online via social media. Changes in knowledge, attitudes, and behavior in eating habits and physical activity frequency can all have an impact on a person's nutritional status and health. The population of this cross-sectional study is followers of @dietsantuy.id who meet the inclusion criteria. A purposive sampling technique was used to select 110 respondents for this study. The instruments used were questionnaires on balanced nutrition knowledge, attitudes, and behavior, eating habits, Food Frequency Questionnaire (FFQ), global physical activity questionnaire (GPAQ), and influencer content questionnaires via Google form. The results show that behavior has a significant relationship with @dietsantuy.id content, with a p value of 0.001 (p 0.005), whereas knowledge and attitude variables have no significant relationship with @dietsantuy.id content. The existence of a significant relationship between content and behavior demonstrates that Instagram content created by influencers can influence a person's behavior. The lack of a significant relationship between content and balanced nutrition attitudes suggests that other factors, such as age, gender, education level, income level, and other external factors, can influence a person'sÂ knowledge and attitudes